Activization of schoolchildren’s cognitive activity during labor training classes: experiment results - Сушенцев, Олександр (Pedagogy of Higher and Secondary Education, 2014)
Sushentsev O. Ye. Activization of schoolchildren’s cognitive activity during labor training classes: experiment results. The author reveals the course of test work on checking theoretically defined pedagogical conditions of promoting cognitive activity of schoolchildren during labor training classes